COMPARING AN ADAPTIVE DECISIONS MODEL AND HUMAN DECISIONS - Whybark, D. Clay (Academy of Management Journal, 1973)
The article discusses the results of a study where the performance of a decision model was compared to the performance of human decision makers. A simple inventory management game was used to compare the two models. The decision model used in this experiment is an adaptive inventory control model, which is designed to compute an economic order quantity on the basis of forecasts produced by an adaptive exponential smoothing model with a single smoothing constant. Total inventory related costs were used to compare the performance of the adaptive inventory control model and the performance of two different student groups. The results showed that while the decision model did better overall, some students did well.